Women and sustainability in business: A global perspective - (:unkn) unknown (Taylor and Francis, 2016)
Women and Sustainability in Business: A Global Perspective, brings together original research from a dozen countries, concerning the issues and challenges facing women in sustainable business. This is a recurrent topic among researchers, regulators, companies and rating agencies. Governments pay special attention to how women impact the economy when shaping their strategies on economic sustainability. Women’s contribution to business is fundamental to creating a sustainable economy, such that businesses try to strengthen ‘women’s presence’ within their organisations, especially on their boards. Today, sustainable companies cannot survive without strategies involving women. Stakeholders, regulators, NGOs and rating agencies track both women-focused strategies and the corporate sustainability reports of companies. Well-designed strategies for women workers help companies to develop their financial and social sustainability initiatives progressively. This book analyses the practice of women in sustainable business, in terms of company performance, social responsibility, board management, entrepreneurship, employment, education, management, social sustainability, environmental politics and technology, from a wide range of diverse, regional perspectives and highlights the differences between the underdeveloped, developing and developed world. © 2017 selection and editorial matter, Kiymet Çaliyurt; individual chapters, the contributors.